Advances in Laboratory-Scale Hydraulic Fracturing Experiments. (29th July 2020) - Qian, Yelin; Guo, Panpan; Wang, Yixian; Zhao, Yanlin; Lin, Hang; Liu, Yan
Abstract : Hydraulic fracturing has been widely applied to stimulate the natural gas and oil production from unconventional reservoirs. To optimize the design of hydraulic fracturing in this application, an accurate estimation of the initiation and propagation of hydraulic fractures is indispensable. However, it still remains challenging as a result of the complex stress state and geological conditions. On account of their ability to complete control some significant factors and efficient observation of fracture geometry, laboratory-scale hydraulic fracturing experiments have received abundant research attention in recent years. This paper presents a review of the state of the art of laboratory-scale hydraulic fracturing experiments, focusing on the scaling analysis, experimental setup, fracturing fluids, and sample preparation. A discussion of the directions for future research is also provided with the intention of stimulating the development of the experimental technique for investigating hydraulic fracturing.